2019
DOI: 10.3390/jcm8081265
|View full text |Cite
|
Sign up to set email alerts
|

Does the Implementation of a Quality Improvement Care Bundle Reduce the Incidence of Acute Kidney Injury in Patients Undergoing Emergency Laparotomy?

Abstract: Purpose: Previous work has demonstrated a survival improvement following the introduction of an enhanced recovery protocol in patients undergoing emergency laparotomy (the emergency laparotomy pathway quality improvement care (ELPQuiC) bundle). Implementation of this bundle increased the use of intra-operative goal directed fluid therapy and ICU admission, both evidence-based strategies recommended to improve kidney outcomes. The aim of this study was to determine if the observed mortality benefit could be exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Of the included 19 studies, all of studies showed the rate of AKI after surgery, six of these studies [ 11 13 , 27 , 30 , 32 ] also reported postoperative complications other than AKI, only 3 studies [ 16 , 33 , 34 ] were not reported a difference in length of stay (LOS) in the ERAS vs. standard group. Rate of 30-day readmission or reoperation reported in 13 studies [ 9 12 , 15 , 17 , 25 30 , 32 ] and mortality in 8 studies [ 11 , 12 , 14 , 15 , 25 , 26 , 30 , 32 ]. 11 studies adopted the fluid management mode of goal-directed fluid therapy (GDFT) [ 10 17 , 27 , 29 , 30 ], 6 studies used restrictive fluid management intraoperatively [ 9 , 25 , 26 , 28 , 33 , 34 ], and the remaining 2 studies [ 31 , 32 ] did not elaborate the fluid management mode.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the included 19 studies, all of studies showed the rate of AKI after surgery, six of these studies [ 11 13 , 27 , 30 , 32 ] also reported postoperative complications other than AKI, only 3 studies [ 16 , 33 , 34 ] were not reported a difference in length of stay (LOS) in the ERAS vs. standard group. Rate of 30-day readmission or reoperation reported in 13 studies [ 9 12 , 15 , 17 , 25 30 , 32 ] and mortality in 8 studies [ 11 , 12 , 14 , 15 , 25 , 26 , 30 , 32 ]. 11 studies adopted the fluid management mode of goal-directed fluid therapy (GDFT) [ 10 17 , 27 , 29 , 30 ], 6 studies used restrictive fluid management intraoperatively [ 9 , 25 , 26 , 28 , 33 , 34 ], and the remaining 2 studies [ 31 , 32 ] did not elaborate the fluid management mode.…”
Section: Resultsmentioning
confidence: 99%
“…Our initial search yielded 7,441 potentially relevant cohort studies on postoperative complications including AKI occurring with ERAS versus conventional therapy in patients who underwent surgery. After screening and reviewing, 19 studies [9][10][11][12][13][14][15][16][17][25][26][27][28][29][30][31][32][33][34] met our inclusion criteria. Of the nineteen, seventeen were retrospective and two were prospective cohort studies.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although less common, cardiovascular and renal complications on any postoperative day were highly predictive of mortality, other major studies of non-cardiac surgery have found that cardiovascular complications are highly predictive of mortality [ 48 , 49 ]. Acute kidney injury is also common in patients undergoing EL and predicts mortality [ 50 , 51 ].…”
Section: Ensuring the Safe Care Of The Emergency Laparotomy Patient P...mentioning
confidence: 99%
“… 3 Electronic health records are prohibitively expensive in resource-constrained settings. The application of AKI bundle interventions has yielded mixed results in terms of benefit in reducing AKI rates, 8 , 9 with even less evidence of benefit from individual interventions such as avoidance of nephrotoxins and overzealous fluid resuscitation, raising the possibility of heightened awareness and improved care quality as the reason for improvement rather than the interdependence of the interventions.…”
Section: Challenges With Models’ Application In Resource-constrained ...mentioning
confidence: 99%